2019
DOI: 10.1186/s12916-019-1259-z
|View full text |Cite
|
Sign up to set email alerts
|

Are China’s oldest-old living longer with less disability? A longitudinal modeling analysis of birth cohorts born 10 years apart

Abstract: BackgroundChina has transitioned from being one of the fastest-growing populations to among the most rapidly aging countries worldwide. In particular, the population of oldest-old individuals, those aged 80+, is projected to quadruple by 2050. The oldest-old represent a uniquely important group—they have high demand for personal assistance and the highest healthcare costs of any age group. Understanding trends in disability and longevity among the oldest-old—that is, whether successive generations are living l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 79 publications
2
31
0
Order By: Relevance
“…Recently, two successive cohorts study from China also present consistent with the results of these developed countries [23,24]. Liu et al demonstrated that the life expectancy of the population ages 90-99 was 3.9-4.0 years [23].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Recently, two successive cohorts study from China also present consistent with the results of these developed countries [23,24]. Liu et al demonstrated that the life expectancy of the population ages 90-99 was 3.9-4.0 years [23].…”
Section: Discussionsupporting
confidence: 57%
“…The life expectancy for 90-year-olds (ranging 4 -5 years) is still reasonably short than that for an 80-year-old (ranging 8 -10 years) [10,11,21,22]. Recently, two successive cohorts study from China also present consistent with the results of these developed countries [23,24]. Liu et al demonstrated that the life expectancy of the population ages 90-99 was 3.9-4.0 years [23].…”
Section: Discussionmentioning
confidence: 85%
“…Recently, two successive cohort studies from China presented results consistent with the results from developed countries [22,23]. Liu et al demonstrated that the life expectancy of the population aged 90-99 years was 3.9-4.0 years [22].…”
Section: Discussionmentioning
confidence: 73%
“…The life expectancy for 90-year-olds (ranging from 4 to 5 years) in most high-income countries is still reasonably shorter than that for 80-year-olds (ranging from 8 to 10 years) [21]. Recently, two successive cohort studies from China presented results consistent with the results from developed countries [22,23]. Liu et al demonstrated that the life expectancy of the population aged 90-99 years was 3.9-4.0 years [22].…”
Section: Discussionmentioning
confidence: 75%
“…During the in-depth study, the Chinese Center for Disease Control and Prevention (CDC) local network medical doctors conducted physical examinations of the participants, and also collected biomarker datasets contain about 30 indicators on routine blood tests, urine tests and blood biochemical tests(41). More detailed descriptions have been previously published elsewhere(44)(45)(46).…”
mentioning
confidence: 99%